Avaliação ecológico-econômica do manguezal de Macau/RN e a importância da aplicação de práticas preservacionistas pela indústria petrolífera local - Rocha Junior, Josenberg Martins da (2011)
This work presents the results of a survey in oil-producing region of the Macau City, northern coast of Rio Grande do Norte. All work was performed under the Project for Monitoring Environmental Change and the Influence of Hydrodynamic forcing on Morphology Beach Grass Fields, Serra Potiguar in Macau, with the support of the Laboratory of Geoprocessing, linked to PRH22 - Training Program in Geology Geophysics and Information Technology Oil and Gas - Department of Geology/CCET/UFRN and the Post-Graduation in Science and Engineering Oil/PPGCEP/UFRN. Within the economic-ecological context, this paper assesses the importance of mangrove ecosystem in the region of Macau and its surroundings as well as in the following investigative exploration of potential areas for projects involving reforestation and / or Environmental Restoration. At first it was confirmed the ecological potential of mangrove forests, with primary functions: (i) protection and stabilization of the shoreline, (ii) nursery of marine life, and (iii) source of organic matter to aquatic ecosystems, (iv) refuge of species, among others. In the second phase, using Landsat imagery and techniques of Digital Image Processing (DIP), I came across about 18,000 acres of land that can be worked on environmental projects, being inserted in the rules signed the Kyoto Protocol to the market carbon. The results also revealed a total area of 14,723.75 hectares of activity of shrimp production and salting that can be harnessed for the social, economic and environmental potential of the region, considering that over 60% of this area, ie, 8,800 acres, may be used in the planting of the genus Avicennia considered by the literature that the species best sequesters atmospheric carbon, reaching a mean value of 59.79 tons / ha of mangrove